2013
DOI: 10.1371/journal.pone.0074369
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic Saline Solution Drives Neutrophil from Bystander Organ to Infectious Site in Polymicrobial Sepsis: A Cecal Ligation and Puncture Model

Abstract: The effects of hypertonic saline solution (HSS) have been shown in several animal models of ischemia and shock. Literature has shown potential benefits of HSS modulating inflammatory response after sepsis in an animal model. We studied the HSS effects in sepsis through cecal ligation and puncture (CLP) in Balb-C mice. Groups studied: 1- CLP without treatment (CLP-C); 2- CLP treated with normal saline solution NaCl 0.9% – 34 ml/Kg (CLP-S); 3- CLP treated with HSS NaCl 7.5% – 4 ml/Kg (CLP-H); and 4- group (Basal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Tumor necrosis factor-! and IL-1" are considered pivotal mediators of lung inflammation in acute respiratory distress syndrome (ARDS) (13,24). The release of TNF-!…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor necrosis factor-! and IL-1" are considered pivotal mediators of lung inflammation in acute respiratory distress syndrome (ARDS) (13,24). The release of TNF-!…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the present study, we investigated whether the failure of neutrophil migration in sepsis and distant organ infiltration were prevented by LPS tolerance. The cecal ligation and puncture (CLP) model was selected for this study because it closely resembles the course of human sepsis (23,24). Here we report that LPS tolerance is associated with a substantial reduction in distant organ damage (lung) and sustained ability for neutrophil infiltration at the infectious site (peritoneal) after CLP challenge.…”
Section: Introductionmentioning
confidence: 99%
“…20 In spite of an inhibitory effect on neutrophil function, Bahrami et al 27 report that in a murine model of very severe hemorrhagic shock, with arterial blood pressure reduced to and kept at 30-35 mm Hg for two hours, no reduction in mortality was observed following hypertonic saline, or hypertonic saline plus hydroxyl ethyl starch. Theobaldo et al, 28 employed a mouse model of cecal ligation and puncture and showed that hypertonic saline drives neutrophils from bystander organs to an infectious site in polymicrobial sepsis: a cecal ligation and puncture model.…”
Section: Neutrophil Functionmentioning
confidence: 99%
“…Experimental studies are confident about the benefits of hypertonic solution use (6)(7)(8). Previous studies have shown that a hypertonic solution reduces the inflammatory profile of endotoxemia in septic mice, as well as pulmonary fibrosis (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that a hypertonic solution reduces the inflammatory profile of endotoxemia in septic mice, as well as pulmonary fibrosis (7)(8)(9). Although the use of hypertonic saline resuscitation presents benefits in controlling the inflammatory process and in reducing mortality in experimental models, clinical trials have failed to demonstrate these same effects (10,11).…”
Section: Introductionmentioning
confidence: 99%